Az erdélyi magyarok és a románok közösségi identitása a társadalmi struktúra tükrében (Szociológiai Szemle, 2024)
The topic of the paper is the analysis of the formation of collective identity and the manifestation of people who live in ethnically mixed areas. Collective identity, and especially national identity, manifests itself in different modalities in keeping with the social status of the persons, and this aspect has to be kept in view for an adequate analysis of collective identity. I would like to present the analysis especially for Western Romania called Transylvania.For obtaining a view of the social structure, we analysed the social stratification using an adaptation of the Erikson - Goldthorpe model. The differentiated analysis of identity according to social stratification is necessary because the identity scheme, the national and political socialisation levels are different in the case of intellectuals and of manual workers.For empirical analysis the main source was the databases from the "Carpathian Basin" project (Nov. 1997), with a representative sample of 1841 persons from Transylvania, with an over-represented Hungarian sub-sample of 1126 cases.By analysing the collective identification from a social stratification perspective, we can notice that the cultural dimension of the identity of persons belonging to the social strata of the higher status and qualification is stronger than that of the persons with a low social status. At the same time, the civic (citizen) dimension of the identity of persons with low social status is relatively stronger. The role of citizenship is more important among the Romanian majority than among the Hungarian minority. The role of exclusive, ethnocentric attitudes is greater among the Romanians from Northern Transylvania (Cluj-Kolozsvar, Oradea zone) than in Southern Transylvania (Brasov, Sibiu-Hermannstadt zone).Common elements can be found in both the collective identity of the majority and minority, which - in spite of social and regional differences - show us that the nation-building processes are completed and the national identity structures are well defined. In case of the majority we can observe a gradual decrease of the importance of the type of cultural national identity.